TransformerLess Partial Voltage DC–DC Converter With Double Power Processing Capacity - Thierry A. Meynard; Hugues Renaudineau; Polidoro S. Canales; Samir Kouro; Diego Concha; Ana M. Llor; Maurice Fadel; Henri Schneider (IEEE Open Journal of the Industrial Electronics Society)
The concept of partial power converters is promising since it might bring significant cost, weight, volume, and power losses reduction. However, most partial power converters presented in the literature include a high-frequency transformer to redirect power from one part of the circuit to another, which adds cost, weight, volume and losses, and cancels out most of the potential advantages introduced by the partiality concept. In this article two variants of a transformerless partial voltage converter capable of supplying twice the power of conventional converters are described and analyzed. These converters can be used for applications in which the load voltages can be split into several sub-voltages of similar characteristics, which makes it typically applicable to batteries, fuel cells, electrolyzers and LEDs. Two main conditions are required to use these topologies: first, the voltage across the load needs to be controlled in a limited range only, typically [50%;100%] or less, and second, it must be possible to split easily the load voltages in several smaller dc voltages. Nevertheless, these restrictions still allow a wide range of possible applications including electrochemical loads such as batteries, fuel cells, electrolyzers, and even PV systems. Their main properties are analyzed and confirmed by experimental results. The lack of transformer and the partial power processing capabilities of the topologies result in extremely high efficiencies of over 99%.